Parry Romberg Syndrome: a case report - Liaquat, Admad; Riaz, Nabeela; Shah, Arun Kumar (Journal of Chitwan Medical College, 2020)
Parry Romberg syndrome (PRS) is a rare disorder, characterized by unilateral facial atrophy of the skin, subcutaneous fat, muscles, cartilages, and even bone. Various systemic manifestations reported with this syndrome are neurologic, maxillofacial, and ophthalmologic. The etiology is still unknown. Herein we present a case report of 23 years young engineering student who had PRS and got a fracture of the right angle of his mandible after a road traffic accident. The treatment was challenging as he had nonunion at the fracture site.